Characterization Of Neurons In The Visceral Ganglia Of The Green-Lipped Mussel (Perna Canaliculus) Using Antibodies Raised Against Neuropeptides And Neurotransmitters - Mahmud, S; Mladenov, PV; Sheard, P; Chakraborty, SC (Bangladesh Journal of Animal Science, 2012)
Central neurons in the visceral ganglia of both male and female Green lipped mussel, Perna canaliculus were characterized by immunohistochemical techniques. We used mollusc antibodies raised against neuropeptides and neurotansmitters known to control reproduction and spawning. Anti-ELH and anti-APGWamide showed very strong immunoreactivity in small type of neurons. Anti-5-HT and anti-DA immunoreactivity was mostly in large type of neurons. The labelled neurons are consistent with descriptions of neurosecretory cells implicated in the control of reproduction and spawning on the basis of earlier histological staining techniques used in this species. The use of selective immunological markers for peptides and amines appears to be a promising tool for further Characterization of neurosecretory cells. To isolate and characterise neuropeptides and other biologically active materials involved in the control of reproduction in Perna canaliculus. DOI: http://dx.doi.org/10.3329/bjas.v37i1.9873 BJAS 2008; 37(1): 78-85